The life-history of short-tailed shearwaters (Puffinus tenuirostris) in response to spatio-temporal environmental variation - Vertigan, CA (2010)
Ecological changes in the phenology and distribution of plants and animals mediated by changes in the environment are occurring across the globe and have been documented for a wide range of species. However, determining the specific mechanisms that affect the life-history parameters of organisms is typically difficult. Measuring population trends over time, and in relation to broad-scale environmental state, is one of the simplest ways of linking the effects of physical environmental variation to its direct effects on biological systems. This study is concerned with describing key life-history parameters and population demography of a wide-ranging and abundant pelagic seabird, the short-tailed shearwater (Puffinus tenuirostris). The population demography of this uppertrophic consumer is investigated directly within the context of its spatio-temporal use of the marine environment and its response to environmental variation. In this thesis I present data and analyses for: 1. Population trends of short-tailed shearwaters and the sympatrical/y breeding little penguin (Eudyptula minor) - Trends from a colony of shorttailed shearwaters at the southern most extent of their distribution were documented from 2003-1 O and found to be declining at a rate of 15% per annum. A series of hypotheses were constructed to provide possible explanations for the observed trends including source-sink population dynamics, recreational 'mutton-birding', by-catch from fisheries, investigator effects, changes in onshore habitat characteristics, and distal changes in food source availability. In contrast little penguins were found to be increasing at a rate of 17% per annum with their increase attributed to the removal of feral cats from Wedge Island in 2003. 2. The effects of investigator disturbance on short-tailed shearwaters and little penguins - Researcher activities were monitored during the course of the study to identify any possible effects on rate of egg laying, chick survival or chick handling. No effect of the investigator was ...